Os parques naturais municipais da ilha de Vitória (ES) no contexto das áreas verdes urbanas : um olhar biogeográfico pelo viés da ecologia da paisagem - Carvalho, Monique Santiago de (2012)
This research is an landscape's interpretation of the Vitoria's island, in Espirito Santo State, of southeast os Brasil, focusing on urban green areas represented by six Natural Municipal Parks. Was used the theoretical assumptions of Landscape Ecology and Biogeography. The landscape can be interpreted by its composition and configuration, and this research, these aspects have been mapped, including the Municipal Park in individual selected as clipping. It was possible to identify, map and characterize the forms and landscape elements. The parks are covered by Atlantic Forest vegetation, and differ as to its dimensions, use and occupation, among other things. It was observed the spatial distribution of parks relative to each other and some possibilities considered as the connectivity between them. The methodology was divided into office and field activity. The mapping procedure was essential to the use of theoretical and methodological framework adopted and from there the discussion develops. It was therefore possible to argue, to map and measure some features of the landscape of the Vitoria's island, such as natural parks, in the context of urban green areas.